Role of Supervisor’s Communication in Employee Engagement & Employee Wellbeing - Veshne, Nupur (Ushus Journal of Business Management, 2017)
Communication is the base to the smooth functioning of organizations and which plays a vital role in maintaining and developing organizations. The growth of an organization is seen through workplace efficiency which is dependent on employee wellbeing. Employee wellbeing affects how employees think and feel about their job and organization in turn which would positively or negatively influence their attitude and performance. Supervisor’s communication can greatly influence the employee’s workplace efficiency. This paper focuses on analyzing the role of supervisor’s communication in employee wellbeing and employee engagement. It identifies the main factors that affect employee wellbeing in the organization. It is evident from the research that organizations need to focus on improving the supervisor’s communication which will enhance employee wellbeing and employee engagement and result into positive attitude and improved performance on the job.